Equilibrium and Kinetic Folding Pathways of a TIM Barrel with a Funneled Energy Landscape - Finke, John M. (Biophysical Society, 2005)
The role of native contact topology in the folding of a TIM barrel model based on the α-subunit of tryptophan synthase (αTS) from Salmonella typhimurium (Protein Data Bank structure 1BKS) was studied using both equilibrium and kinetic simulations. Equilibrium simulations of αTS reveal the population of two intermediate ensembles, I(1) and I(2), during unfolding/refolding at the folding temperature, T(f) = 335 K. Equilibrium intermediate I(1) demonstrates discrete structure in regions α(0)-β(6) whereas intermediate I(2) is a loose ensemble of states with N-terminal structure varying from at least β(1)-β(3) (denoted I(2A)) to α(0)-β(4) at most (denoted I(2B)). The structures of I(1) and I(2) match well with the two intermediate states detected in equilibrium folding experiments of Escherichia coli αTS. Kinetic folding simulations of αTS reveal the sequential population of four intermediate ensembles, I(120Q), I(200Q), I(300Q), and I(360Q), during refolding. Kinetic intermediates I(120Q), I(200Q), and I(300Q) are highly similar to equilibrium αTS intermediates I(2A), I(2B), and I(1), respectively, consistent with kinetic experiments on αTS from E. coli. A small population (∼10%) of kinetic trajectories are trapped in the I(120Q) intermediate ensemble and require a slow and complete unfolding step to properly refold. Both the on-pathway and off-pathway I(120Q) intermediates show structure in β(1)-β(3), which is also strikingly consistent with kinetic folding experiments of αTS. In the off-pathway intermediate I(120Q), helix α(2) is wrapped in a nonnative chiral arrangement around strand β(3), sterically preventing the subsequent folding step between β(3) and β(4). These results demonstrate the success of combining kinetic and equilibrium simulations of minimalist protein models to explore TIM barrel folding and the folding of other large proteins.